Capacity of Mangrove Fruit Macerate (Sonneratia alba) as a Preservative Fresh Vannamei Shrimp (Litopenaeus vannamei) Meat: Kapasitas Maserat Buah Mangrove (Sonneratia alba) sebagai Pengawet Daging Udang Vannamei (Litopenaeus vannamei) Segar - Wicaksono, Agung; Pramudya, Arkan Setia; Zaki, Ekiq Naufal; yachya, Arif (Universitas Muhammadiyah Sidoarjo, 2023)
Mangrove fruit (Sonneratia alba) is known to contain tannins. This flavonoid has antibacterial properties. It makes this fruit macerate has potential as a preservative for shrimp meat. This study aimed for determining the ability of S. alba fruit macerate to maintain the quality of vannamei shrimp meat. The study was conducted in a laboratory by exposing fresh vannamei shrimp meat to S. alba fruit macerate. Exposure was carried out by soaking shrimp meat. The concentrations of macerate used were 25, 50, 75, and 100%. The duration of soaking was 60 and 120 minutes. Bacterial population (total plate count), presence of hydrogen sulfide gas (H2S), acidity value (pH), and score of organoleptic were used as indicators of Shrimp meat quality. The tests were conducted after 24 hours of incubating shrimp meat at room temperature. The results showed the concentration of macerate and the time of soaking affected the quality of the shrimp meat. These effects were in the form of inhibition of bacterial populations, production of H2S and maintaining organoleptic properties, while the pH values ​​of all treatments were the same. Finally, the best concentration of macerate to maintain the quality of fresh vannamei shrimp meat is 100% with 60 minutes of soaking time.